Dysregulation of Hypothalamo-Pituitary-Adrenocortical Axis in Overweight Female Diabetic Subjects is Associated with Downregulation of Corticosteroid Receptors and 11β-HSD1 in the Brain - Li, S.; Liao, Y.; Wang, L.; Huang, R.; Yue, J.; Xu, H.; Zhou, H.; Lou, Z.; Hu, Y.; Liu, W. (Hormone and Metabolic Research, 2016)
The objective of this work was to assess hypothalamo-pituitary-adrenocortical (HPA) axis dysregulation in overweight diabetic women and investigate the possible mechanism using overweight diabetic rats. Twenty-two overweight diabetic women were recruited alongside 34 lean and 23 overweight healthy women serving as controls. Dexamethasone suppression test (0.25 mg DST) and low dose adrenocorticotropic hormone (ACTH) stimulation assay were used to evaluate the HPA axis activity. Then, high fat diet (HF) and STZ-induced diabetic rats were utilized to investigate the possible mechanism. After measurement of corticosterone circadian patterns and dexamethasone suppression levels, mRNA amounts of mineralocorticoid receptors (MR), glucocorticoid receptors (GR), and 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) were determined by real time PCR at hippocampus, hypothalamus, and pituitary levels. Overweight diabetic women showed impaired HPA axis with negative feedback efficacy (suppression ratio F-DEX%: 0.52±0.06% vs. 0.49±0.06% vs. 0.14±0.08%), as well as increased adrenal cortisol secretion response to low dose ACTH stimulation. Interestingly, F-DEX% was negatively correlated with BMI (r=− 0.323, p=0.003), waist circumference (r=− 0.319, p=0.004), and HbA1c (r=− 0.334, p=0.002). Stepwise linear regression analysis showed F-DEX% was significantly related to HbA1c level (β=− 0.328, p=0.007) after adjusting for other covariates (age, BMI, waist circumference, SBP, TC, TG, and HOMA-IR). Furthermore, 11β-HSD1, MR, and GR mRNA expression levels were reduced at pituitary level while GR expression was downregulated at hippocampus level in HF and HF+STZ rats. In conclusion, hyperactive HPA axis in overweight diabetic subjects may be associated with downregulation of 11β-HSD1, MR, and GR in the brain.
Keywords: overweight; diabetes; HPA axis activity; corticosteroid receptors; 11β-HSD1